Clinical Profile of RT-PCR Positive Paediatric Patients with COVID 19: Overview from Chattogram, Bangladesh - Choudhury, Zabeen; Haque, Salina; Das, Aparup Kanti; Choudhury, Sumana; Hira, Hasina Momotaj (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Coronavirus diseases 2019 (COVID-19) has become global pandemic. During the COVID-19 pandemics, caused by SARS-CoV-2, overall, children younger than 18 years are thought to account for only 1% to 2% of detected cases worldwide. COVID-19 has been found less frequent in children and studies on pediatric COVID-19 have also been less reported, especially from Bangladesh. To evaluate the clinical profile of RT-PCR- positive paediatric patients with COVID 19 in Chattogram region. Materials and methods: This cross-sectional study was conducted in OPD, Department of Paediatrics, Chittagong Medical Colllege Hospital (CMCH) Chattogram. All postCOVID paediatric patients reported as RT-PCR positive by Microbiology department of CMCH were enrolled in the study. The study was carried out from 1/8/21 to 31/01/22. According to inclusion/exclusion criteria 96 RT-PCR positive COVID-19 paediatric patients were taken as sample by convenient sampling for this study. The diagnosis of COVID 19 infection was confirmed by RTPCR report of nasopharyngeal or oro-pharyngeal swab. Patients, guardians were contacted over telephone to attend paediatric OPD of CMCH for clinical information & laboratory findings. Results: Among them 96 children, 68.8% were in >5 years, 18.8% were in 1-5 years, and 12.4% were in the <1 year age group; 55.2% were female and 48.8% were male. About 66 (80%) patients had history of contact with suspected or confirmed COVID-19 patient. Total 21 patients got hospitalized. Mean ± SD of time from symptom onset to hospital admission was 4.76 ± 1.998 days. Duration of hospital stay was ranged from 4-14 days. Mean ± SD duration of hospital stay was 6.1 ± 2.385 days. Maximum (97.9%) patients had fever, 77.1% patients had cough and 29.2% patients had vomiting. Majority (82.3%) of the patients had no co-morbidities. Mean ± SD Hb% (g/dl) was 12.04 ± 1.817 g/dl with range: 7-16 g/dl; median (IQR) WBC (/Cumm) was 9500 (720016000) (Range: 3200-26000), median (IQR) Neutrophil (%) was 64 (54-71) (range: 14-90), median (IQR) Lymphocyte (%) was 28 (22-36) (range: 6-74) and median (IQR) Platelet count (/Cumm) was 200000 (172500284000) (Range: 40000-418000). Raised CRP, D-Dimer and S. Ferritin level were found among 43 (75.4%), 8 (14.4%) and 38 (66.7%) patients respectively. Available CXR findings of 47 patients showed that, 21 (45%) had patchy opacity, 19 (40%) had no significant abnormality and 6 (13%) had bilateral consolidation. Paracetamol was the most frequently (83.2%) used drug for this infection. Oral antibiotic was used in 64.2% children, bronchodilator and zinc supplementation were given to 48.4% and 43.2% children respectively. Oxygen therapy was needed for 12.6% children. More than half (57.7%) of the patients reported to feel fatigue after COVID-19 infection. About 40.4% patients had shortness of breath, 38.5% patients had history of weight loss. And 25% patients had lost their taste/smell. Conclusion: Clinical presentations of COVID-19 in children were mild. Fever and cough were found to be the predominant symptoms of COVID-19 affected children in this study. Vomiting, nasal congestion and altered smell were also typical symptoms. Raised CRP and S. Ferritin level were two important laboratory findings. JCMCTA 2022 ; 33 (1) : 124-131